2018
DOI: 10.1038/s41418-017-0038-7
|View full text |Cite
|
Sign up to set email alerts
|

BRAP-2 promotes DNA damage induced germline apoptosis in C. elegans through the regulation of SKN-1 and AKT-1

Abstract: As part of the DNA damage response (DDR) network, the tumour suppressor Breast cancer susceptibility gene 1 (BRCA1) is activated to facilitate DNA repair, transcription and cell cycle control. BRC-1, the Caenorhabditis elegans ortholog of BRCA1, has conserved function in DNA double strand break repair, wherein a loss of brc-1 results in high levels of germline apoptosis. BRAP2/IMP was initially identified as a BRCA1 associated binding protein and previously we have shown that the C. elegans brap-2 deletion mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…This journal is © The Royal Society of Chemistry 2022 expression, 37 and the PMK-1 and p38 MAPK pathways are involved in stress and aging. 38 The skn-1 transcription factor regulates the transcriptional level of gcs-1.…”
Section: Food and Function Papermentioning
confidence: 99%
“…This journal is © The Royal Society of Chemistry 2022 expression, 37 and the PMK-1 and p38 MAPK pathways are involved in stress and aging. 38 The skn-1 transcription factor regulates the transcriptional level of gcs-1.…”
Section: Food and Function Papermentioning
confidence: 99%
“…Emerging evidence suggests that SOD2 is the downstream of SIRT3, which is located in mitochondria and attenuated mitochondrial ROS (Katwal et al, 2018). In our previous study, a major upstream of SIRT3 that has been proved is NRF2, which is encoded as SKN1 gene on C. elegans (Gao et al, 2018;D'Amora et al, 2018). Our results demonstrated that TLB upregulated the protein expressions of SKN1 and SIRT3, thereby exerting its anti-oxidantive effect; whereas, the anti-oxidantive effect of TLB were almost eliminated in SKN1 and SIRT3 mutant C. elegans, which indicated that NRF2/SIRT3 signaling pathway was involved in the anti-aging effects of TLB in C. elegans.…”
Section: Discussionmentioning
confidence: 89%
“…A recent report showed that BRAP2 knockdown led to an increase in the phosphorylation levels of Akt and mTOR in glioma cells (38), and our result was consistent with that report. BRAP2 binds PHLPP1 (27,39) which is involved in Akt activation (28,29), and it has been suggested that BRAP2 suppresses Akt through PHLPP1 to promote apoptosis induction (39). Therefore, we thought that the phosphorylation level of Akt may have been increased because BRAP2 deletion could not suppress Akt through PHLPP1.…”
Section: Discussionmentioning
confidence: 91%